Application of PS2M Aptamer as Receptor Layer for Electrochemical Detection of Lead Ions - Izabela Zaras; Olga Kujawa; Marcin Olszewski; Marta Jarczewska (Biosensors)
Since lead can cause severe effects on living organisms’ health and life, the regular monitoring of Pb levels in water and soil is of particular significance. Recently, it was shown that lead ions can also be detected using affinity-based biosensors, namely, using aptamers as recognition elements. In most cases, thrombin binding aptamer (TBA) was utilized; however, there are more examples of DNA aptamers which could also serve that purpose. Herein, we present studies on the electrochemical detection of lead ions using PS2M aptamer, which contains several guanine nucleotides, as the receptor element. Firstly, the method of aptamer-based layer fabrication was optimized along with the choice of a redox active indicator, which was a source of current signal. The experiments revealed the possibility of lead ion detection from 50 to 600 nM, which covers the range below and above the maximum accepted limit stated by US EPA (72 nM). Moreover, the sensing layer exhibited high selectivity towards lead ions and was successfully applied both for the analysis of tap water spiked with Pb2+ ions and as a miniaturized sensor. Finally, stability and regeneration studies on the aptamer-based receptor layer were executed to confirm the utility of the elaborated tool.